2009
DOI: 10.5194/angeo-27-199-2009
|View full text |Cite
|
Sign up to set email alerts
|

Coupled rotational dynamics of Jupiter's thermosphere and magnetosphere

Abstract: Abstract.We describe an axisymmetric model of the coupled rotational dynamics of the thermosphere and magnetosphere of Jupiter that incorporates self-consistent physical descriptions of angular momentum transfer in both systems. The thermospheric component of the model is a numerical general circulation model. The middle magnetosphere is described by a simple physical model of angular momentum transfer that incorporates self-consistently the effects of variations in the ionospheric conductivity. The outer magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
143
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(146 citation statements)
references
References 51 publications
3
143
0
Order By: Relevance
“…Typical values for the auroral electron characteristics are highlighted in bold in Table 2 and yield Pedersen conductance values in the 1.5-2 mho range at Jupiter and in the 10-15 mho range at Saturn (see Table 2). These jovian values are supported by estimations from field-aligned potential models -using parameterized Pedersen conductance relations: they spread from 0.7 to 1.5 mho (Smith and Aylward 2009;Tao et al 2009;Ray et al 2010). Therefore, difference in auroral forcing reduces the difference in conductances between Jupiter and Saturn down to one order of magnitude.…”
Section: Ionospheric Electrical Conductancesmentioning
confidence: 78%
See 3 more Smart Citations
“…Typical values for the auroral electron characteristics are highlighted in bold in Table 2 and yield Pedersen conductance values in the 1.5-2 mho range at Jupiter and in the 10-15 mho range at Saturn (see Table 2). These jovian values are supported by estimations from field-aligned potential models -using parameterized Pedersen conductance relations: they spread from 0.7 to 1.5 mho (Smith and Aylward 2009;Tao et al 2009;Ray et al 2010). Therefore, difference in auroral forcing reduces the difference in conductances between Jupiter and Saturn down to one order of magnitude.…”
Section: Ionospheric Electrical Conductancesmentioning
confidence: 78%
“…Finally, Smith and Aylward (2009) found negative values of k in the ionospheric regions mapping to magnetospheric radii inside of 20 R J as a result of super-rotation of the neutrals.…”
Section: Ionospheric Electrical Conductancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other theoretical studies of the magnetosphere-ionosphere coupling have included more realistic, global-circulation models for the thermosphere-ionosphere (e.g. Achilleos et al 2001;Smith and Aylward 2009;Yates et al 2012). The most recent study of this kind (Yates et al 2012) found that the total energy transferred from the planet's rotation to the atmosphere and magnetosphere varies with magnetodisc size.…”
Section: Overviewmentioning
confidence: 99%